Global East Asia : into the twenty-first century - Pieke, Frank N.; Iwabuchi, Kōichi, 1960- (Global square, 2021)
"Drawing on work in a range of disciplines-including history, anthropology, demography, development, environmental studies, political studies, health, sociology and the arts-this work approaches East Asia from new perspectives.The book looks at contemporary Japan and Korea and focuses on many facets of Chinese culture, artistic production, economic development, digital issues, education and international collaboration" -